Implementation of SINERGIS disc to increase knowledge of PROLANIS member in monitoring diabetes mellitus independently during COVID-19 pandemic - Abiyyu Naufal Susanto; Maryana Maryana; Titik Fajriyati Nur Khasanah; Wahyu Febriana; Joko Tigo Narimo Bekti (Poltekkes Kemenkes Yogyakarta, 2021)
Diabetes mellitus is a disease of blood sugar, protein, and fat metabolism disorders which is often referred to as